Functional Characterization of 17 Protein Serine/Threonine Phosphatases in Toxoplasma gondii Using CRISPR-Cas9 System - Liang, Qin-Li; Nie, Lan-Bi; Li, Ting-Ting; Elsheikha, Hany M.; Sun, Li-Xiu; Zhang, Zhi-Wei; Zhao, Dan-Yu; Zhu, Xing-Quan; Wang, Jin-Lei (Frontiers in Cell and Developmental Biology, 2022)
Protein serine/threonine phosphatases (PSPs), found in various plants and protozoa, are involved in the regulation of various biological processes. However, very little is known about the role of PSPs in the pathogenicity of the apicomplexan protozoan Toxoplasma gondii. Herein, the subcellular localization of 17 PSPs (PP5, PP7, EFPP, SLP, PPM3F, PPM4, PPM5A, PPM5B, PPM6, PPM8, PPM9, PPM12, PPM14, PPM18, CTD1, CTD2 and CTD3) was examined by 6×HA tagging of endogenous genes in C-terminal. The PSPs were detected in the cytoplasm (PP5, EFPP, PPM8 and CTD2), dense granules (SLP), nucleus (PPM4 and PPM9), inner membrane complex (PPM12), basal complex (CTD3), and apical pole (PP7). The remaining PSPs exhibited low or undetectable level of expression. To characterize the contribution of these genes to the infectivity of T. gondii, knock-out (KO) strains of type Ⅰ RH strain deficient in the 17 psp genes and KO type Ⅱ Pru strain of deficient in pp7 and slp genes were constructed. The pathogenicity of individual RHΔpsp mutants was characterized in vitro using plaque, egress, and intracellular replication assays, and mouse infection, while pathogenicity of PruΔpp7 and PruΔslp mutant strains was evaluated by examining the parasite lytic cycle in vitro and assessment of brain cyst burden in mice. No significant differences were observed between 16 RHΔpsp strains and wild-type (WT) RH strain. However, RHΔpp7 exhibited significantly lower invasion efficiency and parasitophorous vacuole formation in vitro, and low virulence in mice compared to other RHΔpsp and WT strains. In addition, PruΔpp7 exhibited marked attenuation of virulence and significant reduction in the brain cyst burden in mice compared with PruΔslp and WT strains, suggesting the key role of PP7 in the virulence of T. gondii. Comparative transcriptomic profiling of the 17 psp genes showed that they may play different roles in the pathogenesis of different genotypes or life cycle stages of T. gondii. These findings provide new insight into the role of PSPs in the pathogenesis of T. gondii.